2013
DOI: 10.1007/s00234-013-1294-y
|View full text |Cite
|
Sign up to set email alerts
|

Disc degeneration and chronic low back pain: an association which becomes nonsignificant when endplate changes and disc contour are taken into account

Abstract: The association between severe DD and LBP ceases to be significant when adjusted for MC and disc protrusion/hernia. These results do not support that DD as a major cause of chronic LBP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 31 publications
0
16
1
Order By: Relevance
“…Understanding the root cause of pain from degeneration is difficult due to a high prevalence of asymptomatic individuals with disc degeneration. 17 In contrast, pain caused by a herniated disc may be easier to identify as the protruding material impinges on spinal nerves, resulting in low back pain and/or sciatica (i.e., radiating leg pain).…”
Section: Introductionmentioning
confidence: 99%
“…Understanding the root cause of pain from degeneration is difficult due to a high prevalence of asymptomatic individuals with disc degeneration. 17 In contrast, pain caused by a herniated disc may be easier to identify as the protruding material impinges on spinal nerves, resulting in low back pain and/or sciatica (i.e., radiating leg pain).…”
Section: Introductionmentioning
confidence: 99%
“…Lumber disc degeneration is a potential cause of low back pain (LBP). Though disc degeneration itself is not diagnostic for LBP (1)(2)(3)(4), in a recent meta-analysis for adults 50 years of age or younger, Brinjikji et al (5) reported disc degeneration is associated with LBP (OR, 2.24; 95% CI, 1.21-4.15; P=0.01). Many studies on magnetic resonance (MR) relaxometry and disc degeneration have been published (6)(7)(8).…”
mentioning
confidence: 99%
“…The association between MCs and LBP has previously been examined in studies with 1-2 year follow-up and one study with 10-year follow-up 17 . Some studies have reported a higher prevalence of LBP in patients with MCs, particularly MC-1, compared to DD alone, while other studies do not find MCs to be associated with LBP [11][12][13]15,16,26 . A systematic review and meta-analysis from 2018 of 31 MCs studies, found the association between MCs and LBPrelated outcomes to be inconsistent 10 .…”
Section: None Of the Patients Had Prolonged Courses Of Antibiotics Aimentioning
confidence: 98%
“…Of the subjects with MCs, 88% reported pain in the past year, compared to 63% of those without MCs. Although back pain and disability have been associated with MC in several studies, the results are still conflicting [10][11][12][13][14][15][16] . The currently available studies are predominantly either crosssectional or with short follow-up, and only one looked at long-term influences 17 .…”
Section: Introductionmentioning
confidence: 99%